EKSISTENSI KUKERTA UNRI DESA SEBANGAR DALAM MENINGKATKAN LITERASI DAN NUMERASI DI SDN 33 BATHIN SOLAPAN - As’ari, Hasim; Malau, Ananda Dwi Putri Br; Sitompul, Agustri Afrianto; Siburian, Alfina Damayanti; Cu, Nina Rivan; Ziada, Salwa; Br Purba, Sazkia Johanna; Putri, Sri; Girsang, Velentina Christina; Sijabat, Yusni Laura (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
This study displays the performance and concern of KUKERTA (Real Work Class) students from the University of Riau who are involved in literacy and numeracy teaching activities at SDN 33 Bathin Solapan, Sebangar Village. The purpose of this study is to describe the implementation of the results of teaching KUKERTA students who are more modern and up-to-date based on lessons for siwi students at SDN 33 Bathin Solapan. This updated learning activity has an impact on the thinking of elementary school students, as well as evaluates students' experiences in participating in these activities. The method used involved participatory observation, teaching sessions, and structured interviews with students and teachers as well as grade 4 and 1 students at the school. Keywords: Implementasi, Kreativitas, Literasi dan Numerasi.